Retrospective Review of Revision Surgery After Image-guided Instrumented Spinal Surgery Compared With Traditional Instrumented Spinal Surgery. Issue 7 (August 2020) - Towner, James E.; Li, Yan Icy; Singla, Amit; Moquin, Ross; Li, Yan Michael
Abstract : Study Design: Retrospective cohort series. Objective: The objective of this study was to determine if the use of image-guided navigation offers a clinically significant advantage over fluoroscopy-assisted pedicle screw and non-navigated screw placement in reducing the risk of revision surgery for malpositioned screws in instrumented spinal surgery. Summary of Background Data: Use image-guided navigation has become increasingly commonplace in instrumented spine surgery, but there is a lack of information regarding differences in the rates of clinically relevant screw malposition with image-guided compared with non-navigated screw placement. Materials and Methods: This is a retrospective cohort series of consecutive patients who underwent instrumented spinal surgery by the senior authors at 2 academic tertiary care centers in New York. Results: A total of 663 instrumented spinal surgeries were analyzed, including 271 instances with image-guided navigation. For the image-guided navigation cohort, 110 of the patients underwent screw placement using O-Arm image-guidance, yielding data on 1115 screws. The remaining 161 surgeries utilizing image-guided screw placement were performed using Brainlab Spine Navigation, for a total of 1001 screws. A fluoroscopy-assisted technique or freehand technique was used in 419 instances, with a total of 3689 screws. Of the non-navigated cohort, 10 patients required a surgical revision of screw placement, for a total of 15 malpositioned screws. Amongst the image-guided navigation cohort, 1 patient in the O-Arm group and 2 in the Brainlab group required revision surgery, with 3 malpositioned screws in total. The rate of revision surgery for a malpositioned screw placed via non-navigated techniques was 2.39%. This risk was decreased to 1.11% with the use of the intraoperative image-guided navigation. However, no comparisons between non-navigated and image-guided screw placement reached statistical significance. Conclusion: Although not reaching statistical significance, these data suggest there may be an advantage offered by image-guided screw placement in instrumented spinal surgery.